2022
DOI: 10.1111/jbi.14516
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping‐by‐sequencing for biogeography

Abstract: Aim: Genotyping-by-sequencing (GBS) and similar reduced-representation sequencing methods, such as restriction site-associated DNA sequencing (RADseq), have been revolutionary for genetic analyses in biogeography. However, navigating the many different methodological and analytical approaches and numerous sources of potential error can be overwhelming. We provide an overview of key considerations for biogeographical research using GBS, from sample design through data filtering to the sharing of data, which sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 282 publications
(400 reference statements)
0
3
0
Order By: Relevance
“…Genotyping by sequencing can discover thousands of genomic variants in non-model species but requires a bioinformatic procedures for data cleaning due to genotyping errors (Mastretta-Yanes et al 2015) and missing data (López de Heredia et al 2020; Vaux et al 2023). This typically includes steps to filter or test for missing data, minor allele frequency, minimum and maximum depth, hardy-weinberg and linkage disequilibrium filtering (Vaux et al 2023), and may involve imputation of missing alleles using statistical methods (López de Heredia et al 2020; Mora-Márquez et al 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Genotyping by sequencing can discover thousands of genomic variants in non-model species but requires a bioinformatic procedures for data cleaning due to genotyping errors (Mastretta-Yanes et al 2015) and missing data (López de Heredia et al 2020; Vaux et al 2023). This typically includes steps to filter or test for missing data, minor allele frequency, minimum and maximum depth, hardy-weinberg and linkage disequilibrium filtering (Vaux et al 2023), and may involve imputation of missing alleles using statistical methods (López de Heredia et al 2020; Mora-Márquez et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Genotyping by sequencing can discover thousands of genomic variants in non-model species but requires a bioinformatic procedures for data cleaning due to genotyping errors (Mastretta-Yanes et al 2015) and missing data (López de Heredia et al 2020; Vaux et al 2023). This typically includes steps to filter or test for missing data, minor allele frequency, minimum and maximum depth, hardy-weinberg and linkage disequilibrium filtering (Vaux et al 2023), and may involve imputation of missing alleles using statistical methods (López de Heredia et al 2020; Mora-Márquez et al 2023). We found 199,704 variants before filtering, which is relatively low compared to the 1.3M SNPs found in Chinese fir ( Cunninghamia lanceolata ) also a member of the Cupressaceae family (Zheng et al 2019) or the 349,542 SNPs found in the foxtail pine ( Pinus balfouriana ) (Friedline et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation